PEMANFAATAN SAMPAH SAYUR PASAR SEBAGAI BIOLISTRIK MELALUI MICROBIAL FUEL CELL UNTUK RANCANGAN HANDOUT MATERI BIOLOGI SMA - Arasyid, Hari; Mahadi, Imam; Darmawati, Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Vegetable waste is a habitat for microorganism that are very threatening to people's health if not managed properly. Management of vegetable waste can be done through a microbial fuel cell while producing useful alternative energy in the form of electricity. This study aims to determine the benefits of market vegetable waste as a biolistric through a microbial fuel cell. This study uses a quantitative approach with a type of Completely Randomized Design (CRD) research. The results showed the highest electrical energy value was obtained in R3 + treatment that is 8.93 mV at an average pH of substrate 4.5, the initial temperature of the substrate 32oC and the final temperature of the substrate 30oC. Based on further Duncan Multiple Range Test (DMRT) at the 5% level, the addition of 50 ml of Effective Microorganism 4 can increase the electrical energy produced in the reactor. It was concluded that vegetable waste can produce electrical energy by utilizing electrochemical cells based on microbial fuel cells.Key words : Vegetable waste, microbial fuel cell, and effective microorganism 4.